Adult Growth Hormone Deficiency – Benefits, Side Effects, and Risks of Growth Hormone Replacement - Reed, Mary L.; Merriam, George R.; Kargi, Atil Y. (Frontiers in Endocrinology, 2013)
Deficiency of growth hormone (GH) in adults results in a syndrome characterized by decreased muscle mass and exercise capacity, increased visceral fat, impaired quality of life, unfavorable alterations in lipid profile and markers of cardiovascular risk, decrease in bone mass and integrity and increased mortality. When dosed appropriately, GH replacement therapy (GHRT) is well tolerated, with a low incidence of side effects, and improves most of the alterations observed in GH deficiency (GHD); beneficial effects on mortality, cardiovascular events and fracture rates, however, remain to be conclusively demonstrated. The potential of GH to act as a mitogen has resulted in concern over the possibility of increased de novo tumors or recurrence of pre-existing malignancies in individuals treated with GH. Though studies of adults who received GHRT in childhood have produced conflicting reports in this regard, long term surveillance of adult GHRT has not demonstrated increased cancer risk or mortality.